UPAYA MENINGKATKAN PEMBELAJARAN LOMPAT JAUH GAYA JONGKOK MELALUI MEDIA BANKAS PADA SISWA KELAS V SD NEGERI 01 KEBOJONGAN KEC.COMAL KAB. PEMALANG TAHUN AJARAN 2013 / 2014 - Diki Meidhoni; Agus Widodo Suripto (Universitas Negeri Semarang, 2015)
The purpose of this study to determine the improvement of learning outcomes with the game long jump long jump squat style through media used tires on students. This research method uses Classroom Action Research (CAR). Subjects were fifth grade students of SD Negeri 01 Kebojongan which amounts to 18 students.The results showed that the long jump squat force through media used tires can increase learning. In the initial conditions show learning results 44.44% (8 students who completed), at cycle 1 shows the results of study 61.11% (11 students who completed) which means it has no increase from the initial condition but has not reached the expected target percentage, while in cycle 2 study results showed an increase of 83.33% (15 students who completed) which means it has reached the expected target percentage. Conclusions from this research is the long jump squat style game through media used tires can improve learning outcomes long jump at the fifth grade students of SD Negeri 01 Kebojongan District of Comal Pemalang Academic Year 2013/2014